2019
DOI: 10.4314/ijs.v21i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and quantification of chemical compounds in selected edible wild leafy vegetables

Abstract: This study identified, characterized and quantified the constituents of Basella alba Linn. var. alba, Crassocephalum crepidioides (Benth.) S. Moore, Launaea taraxacifolia Amin Ex. C. Jeffrey (Wild lettuce), Senecio biafrae Oliv. & Hiern. and Solanum nigrum L. var. virginicum (Black nightshade) leaves. Pulverised dried leaves (10 g each) of the vegetables were separately Soxhlet-extracted with 60 ml of n-hexane (99%). Aliquots (2 μl) of each concentrated plant extract were analysed using gas chromatography-mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…These include n-Hexadecanoic acid, Hexadecanoic methyl ester (palmitic acid) and α-Linolenic acid (ALA) with reported hypocholesterolemic and other lipidlowering properties. Salisu et al (2019) similarly reported high quality match palmitic, oleic and linoleic acids as Ayodele et al 3 major components out of eight compounds identified from GC-MS analysis of n-hexane extract of C. crepidioides leaf. However, this present study identified 64 compounds of phytochemical importance in C. crepidioides leaf hexane fraction obtained from the methanol (crude) extract.…”
Section: Discussionmentioning
confidence: 87%
“…These include n-Hexadecanoic acid, Hexadecanoic methyl ester (palmitic acid) and α-Linolenic acid (ALA) with reported hypocholesterolemic and other lipidlowering properties. Salisu et al (2019) similarly reported high quality match palmitic, oleic and linoleic acids as Ayodele et al 3 major components out of eight compounds identified from GC-MS analysis of n-hexane extract of C. crepidioides leaf. However, this present study identified 64 compounds of phytochemical importance in C. crepidioides leaf hexane fraction obtained from the methanol (crude) extract.…”
Section: Discussionmentioning
confidence: 87%
“…Vitamin E or tocopherol and its various biological forms including gamma and delta tocopherol are predominantly known for their antioxidant properties. Phytol is a terpenoid used as a precursor for synthesis of fat soluble vitamins E and K1 [53] with strong antioxidant and possess anti-inflammatory activity [54]. Lup-20(29)-en-3-ol, acetate, (3β)-, a triterpenoid also known as lupeol acetate possess antimicrobial, antiinflammatory, antimalarial, antituberculosis, antinociceptive and anticancer activity against breast cancer cells MCF-7 [55,56].…”
Section: Resultsmentioning
confidence: 99%
“…In a study, polyunsaturated fatty acids were the main group of fatty acids documented in all the species of coral fungi from Northwestern Himalayas (Sharma & Guatam 2017). These bioactive compounds are known to have potent antimicrobial, antioxidant, anti-inflammatory and antistaphylococcal properties (Ogidi et al 2015;Falade et al 2017;Salisu et al 2019;Akingbesote & Oyetayo 2021). Ogidi (2017) had earlier reported the presence of these groups of fatty acids in bioactive extracts obtained from Lenzites quercina.…”
Section: Discussionmentioning
confidence: 99%